Argumentation in Geography Lessons - Budke, Alexandra (Journal of Geography Education, 2012)
This article concentrates on the advancement of competencies in argumentation during geography lessons. Firstly, the significance of conducting arguments for comprehension intensive learning of geographical contents and individual opinion forming is discussed. Afterwards, two empirical studies are introduced, that deal with the question, to what extent argumentation takes place in geography lessons. Observation of 1414 geography lessons have shown, that only in a small fraction of this amount, arguments are conducted. For interpreting this result, teacher’s statements from qualitative interviews assessing the topic are used.